PENERAPAN STRATEGI SEPAK BOLA VERBAL DENGAN MENGGUNAKAN HANDOUT PADA MATA PELAJARAN BIOLOGI KELAS VIII SMP NEGERI 1 RAO SELATAN KABUPATEN PASAMANPENERAPAN STRATEGI SEPAK BOLA VERBAL DENGAN MENGGUNAKAN HANDOUT PADA MATA PELAJARAN BIOLOGI KELAS VIII SMP NEG - Handayani, Sri; Sudirman, Sudirman; Nerita, S.Pd, M.Pd, Siska (Pendidikan Biologi, 2014)
Biology is one of the subjects of interest by students but there are also students who do not like it. Students who do not like is because learning biology is still centered on teachers and monotonous nature so that students tend to get bored listening to the explanation from the teacher. Attention teachers are also more devoted to the mastery of the material. In addition to the interest, motivation, and learning enthusiasm of students learning low due to less attractive and unattractive teaching materials. Therefore verbal football strategy applied by using handouts in the learning process. The purpose of this research is to improve student learning outcomes by implementing strategies by giving a verbal football handouts.In accordance with the problems and  research objectives, the type of research is experimental research. Experimental research design used in this study is a Randomized Control Group Only Design. The sampling technique used was purposive random sampling, the implementation of the research done in class as class eskperimen VIII.7 class and the class as a class sample VIII.6.The result showed that the experiment class has an average value of 79.69 is higher than the average value of the control class 72.27. After the data were analyzed by t-test, obtained the price ofTcount 2.69 and 1.66 T table. Thus T count > T table which means that H1  is accepted. It can be concluded that the application of verbal football strategy by providing handouts can improve learning outcomes biology eighth grade students of SMP Negeri 1 South Rao.